2015
DOI: 10.1093/mnras/stv2480
|View full text |Cite|
|
Sign up to set email alerts
|

Kinematics of dwarf galaxies in gas-rich groups, and the survival and detectability of tidal dwarf galaxies

Abstract: We present DEIMOS multi-object spectroscopy (MOS) of 22 star-forming dwarf galaxies located in four gas-rich groups, including six newly-discovered dwarfs. Two of the galaxies are strong tidal dwarf galaxy (TDG) candidates based on our luminosity-metallicity relation definition. We model the rotation curves of these galaxies. Our sample shows low mass-to-light ratios (M/L=0.73±0.39M /L ) as expected for young, star-forming dwarfs. One of the galaxies in our sample has an apparently strongly-falling rotation cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Moreover, Sweet et al (2016) observed 22 star-forming dwarf galaxies in four Choir groups with DEIMOS multi-object spectroscopy and analysed the galaxy kinematics, finding two new tidal dwarf galaxy candidates: J1051-17:g11 and J1403-06:g1. The rotation curves of the observed dwarf galaxies are disturbed due to recent interactions (Sweet et al 2016). Moreover, they found that as much as half of the sample may be affected by the tidal interactions with neighbouring galaxies.…”
Section: From Singg To Choirsmentioning
confidence: 99%
“…Moreover, Sweet et al (2016) observed 22 star-forming dwarf galaxies in four Choir groups with DEIMOS multi-object spectroscopy and analysed the galaxy kinematics, finding two new tidal dwarf galaxy candidates: J1051-17:g11 and J1403-06:g1. The rotation curves of the observed dwarf galaxies are disturbed due to recent interactions (Sweet et al 2016). Moreover, they found that as much as half of the sample may be affected by the tidal interactions with neighbouring galaxies.…”
Section: From Singg To Choirsmentioning
confidence: 99%
“…However, earlier observations have found that some galaxies have highly misaligned rotations between stars and gas (e.g., Ulrich 1975;Rubin et al 1992). Moreover, long-slit observations have revealed that galaxies can be misaligned regardless of their mass or morphology (e.g., Bertola et al 1992;Kuijken et al 1996;Kannappan & Fabricant 2001;Sweet et al 2016). Recently, the advent of integral field spectroscopy (IFS) observations has revealed more detailed kinematic properties of misaligned galaxies (e.g., Sarzi et al 2006;Coccato et al 2011Coccato et al , 2015Davis et al 2011;Barrera-Ballesteros et al 2014Serra et al 2014;Krajnović et al 2015;Jin et al 2016;Katkov et al 2016;Bryant et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As stars form from gas, stars and gas of a galaxy are naturally expected to share the same or similar spin orientation, assuming the overall angular momentum is conserved. However, spectral observations have found that some galaxies have different axes of rotation be-tween stars and gases (e.g., Ulrich 1975;Bertola et al 1992;Rubin et al 1992;Kuijken et al 1996;Kannappan & Fabricant 2001;Sweet et al 2016). Moreover, recent integral field spectroscopy (IFS) observations confirmed the presence of misaligned galaxies regardless of the shape and environment (e.g., Sarzi et al 2006;Coccato et al 2011Coccato et al , 2015Davis et al 2011;Serra et al 2014;Barrera-Ballesteros et al 2014Krajnović et al 2015;Katkov et al 2016;Jin et al 2016;Bryant et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(i) Long-slit spectroscopy, such as in RF12, can suffer from misalignment between the kinematic and photometric major axes. The 2D nature of IFS means that the kinematic major axis need not be known a priori (Sweet et al 2016).…”
Section: Specific Angular Momentummentioning
confidence: 99%